PENGARUH MOTIVASI DAN PENGALAMAN KERJA MELALUI PROFESIONALISME TERHADAP KINERJA TENAGA PENDIDIK DI KOMANDO PEMBINAAN DOKTRIN PENDIDIKAN DAN LATIHAN ANGKATAN LAUT (KODIKLATAL) SURABAYA - Hendri Suprianto (Prodi Magister Manajemen Universitas Wijaya Putra, 2017)
The Indonesian naval education and training doctrine maintainance command (Kodiklatal) as one of the Indonesian navy education institution, has the task and responsibility to form the human resource as competence and respected soldiers. The education here are surely the poineers of one of certain factors in reaching the purpose and target. That is why the maintenece of educators must be always conducted continously to gain the professionalism of educators based on the motivation and task experience. Then the performance of Kodiklatal educators hopefully will be must better. The location of this study was conducted at the Indonesian naval education and training doctrine maintenance command (Kodiklatal) of Surabaya. Based on the result of study and hypothesis examination, it was found that the motivation variable on the performance variable trough the professionalism variable has significan result, whereas the task experience variable on the performance variable trough the professionalism variable can be stated as very significan.